2023
DOI: 10.21037/atm-22-3681
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiac troponin testing at scheduled admission and mortality in patients with comorbidities

Abstract: Background: Cardiac troponin I (cTnI) is a gold-standard biomarker for detecting myocardial infarction.Recently, the prognostic role of cTnI was reported for stable coronary artery disease and other chronic diseases. This study aimed to evaluate the usefulness of cTnI testing at scheduled admission of patients with comorbidities.Methods: We retrospectively enrolled patients with comorbidities who were admitted through the outpatient clinic from April 2010 to December 2018. The enrolled patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Oh, AR et al (2023) 9 showed the measurement of cTnI in relatively stable patients at scheduled admission to medical departments was associated with reduced mortality during one year of follow-up. This could be related to more active evaluation and treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Oh, AR et al (2023) 9 showed the measurement of cTnI in relatively stable patients at scheduled admission to medical departments was associated with reduced mortality during one year of follow-up. This could be related to more active evaluation and treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the Oh et al analysis (1) "Association between cardiac troponin testing at scheduled admission and mortality in patients with comorbidities" presents the utility of troponin I screening test basing on the analysis performed on 289,764 consecutive asymptomatic patients who were admitted from the outpatient clinic to non-cardiological/non-cardiac surgery departments.…”
mentioning
confidence: 99%
“…Elevated or at upper normal range levels of troponin may be present in several acute or chronic diseases and associated with worse prognosis (10). Therefore, early changes in pharmacotherapy may influence the long-term outcomes which was underlined in the study by Oh et al (1). Troponin elevation was presented in acute decompensation and liver failure with increased mortality (11).…”
mentioning
confidence: 99%